2007
DOI: 10.3168/jds.2006-683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varying Lactation Length on Milk Production Capacity of Cows in Pasture-Based Dairying Systems

Abstract: The aim of this experiment was to quantify the milk production capacity of cows undergoing extended lactations while fed a pasture-based diet typical of those used in the seasonal-calving dairying systems of Victoria, Australia. One hundred twenty-five Holstein cows were randomly assigned to 1 of 5 groups. Breeding was progressively delayed after calving to enable management of the groups for lactation lengths of 10, 13, 16, 19, and 22 mo (equivalent to calving intervals of 12 to 24 mo). Cows were provided wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 13 publications
(13 reference statements)
9
69
0
4
Order By: Relevance
“…Actually, the possibility of increasing lactation length has been considered as an alternative to the common strategy of maximizing lactation peaks and minimizing calving intervals (Grossman and Koops, 2003;Auldist et al, 2007;Butler et al, 2010). Cows with extended lactations have a reduction of calving risks and of postpartum metabolic diseases (Cole and Null, 2009) with a corresponding decrease in insemination costs and in number of days dry.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the possibility of increasing lactation length has been considered as an alternative to the common strategy of maximizing lactation peaks and minimizing calving intervals (Grossman and Koops, 2003;Auldist et al, 2007;Butler et al, 2010). Cows with extended lactations have a reduction of calving risks and of postpartum metabolic diseases (Cole and Null, 2009) with a corresponding decrease in insemination costs and in number of days dry.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the seasonal calving system is being challenged due to increased herd size, increased use of bought-in feed, premium paid for off-season milk, increased milk production potential, reduced reproductive performance and pressure from animal welfare groups to minimise induced calving (Borman et al, 2004). As a result of these factors, interest in milking cows beyond the standard 305 days (over an extended lactation period) has increased and the proportion of herds that practice seasonal calving in Victoria, Australia, has decreased from 63% to 41% (Auldist et al, 2007). Expected benefits of extended lactations include reduction in insemination costs and in number of days dry within the cow's lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Variation between cows in the ability to maintain lactation after 300 days is large (Bertilsson et al, 1997;Van Amburgh et al, 1997) even in countries where average milk production levels are over 9000 kg of milk. In Australia, where mean milk production varies between 4000 and 7000 kg, a large variation in ability of cows to produce milk after the standard 300 days was observed in an experimental herd (Auldist et al, 2007). The risks associated with delaying mating could be high due to losses in the current and future performance of cows.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Auldist et al (2007) showed a small negative effect and Kolver et al (2007) showed some gains and some losses in milk yield of cows, which had their lactations extended to up to 2 yr in a pastoral system. Furthermore, 2 studies have indicated a potential negative influence of a previous extended lactation on the dry period length and milk yield of the following lactation (Arbel et al, 2001;Österman and Bertilsson, 2003).…”
Section: Effect Of Calving Interval and Parity On Milk Yield Per Feedmentioning
confidence: 99%